Evaluation of a DAS-ELISA for quantification of foot-and-mouth disease virus 146S antigen during vaccine preparation - Quan, Melvyn (University of Pretoria, 2024)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2023.